An application of the nonprofit virtual accountability index: Accountability in sport for development and peace. Issue 3 (21st October 2022) - Svensson, Per G.; Naraine, Michael L.
Abstract: In this research note, we examine web‐based accountability practices of human service nonprofits. Data were collected directly from the organizational websites of an international sample of 532 organizations involved in operating sport for social change programs, more commonly known as the field of sport for development and peace. Websites were coded using the nonprofit virtual accountability index—a theoretically grounded and robust tool—to measure information and interactivity available for stakeholders across five dimensions of accountability. Analyses of variance and independent t ‐tests were used to test potential group differences based on geographical region, the thematic types of social change efforts, and the type of sport used to deliver programming. The results of this analysis highlight the critical importance of geographical location and other organizational variables for web‐based accountability practices. Furthermore, the results allow nonprofit leaders to identify common areas in need of improvement for smaller and emerging nonprofits.